1997
DOI: 10.1017/s0016672396002558
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for regression interval mapping in QTL analysis with non-normal traits

Abstract: We compare the powers of three methods for the QTL analysis of non-normally distributed traits. We describe the nonparametric and the logistic regression approaches recently proposed in the literature and study the properties of the standard regression interval mapping method when the trait is not normally distributed. It is shown that the standard approach is robust against nonnormality and behaves quite well for both continuous and discrete characters. The loss of power compared with the nonparametric or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 14 publications
(8 reference statements)
6
65
0
1
Order By: Relevance
“…We finally used the regression interval mapping method of Haley and Knott (1992) and the nonparametric QTL mapping approach proposed by Kruglyak and Lander (1995), both shown to be robust against the nonnormality of the phenotypes (Rebai 1997). These analyses were implemented using R/QTL (Broman et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…We finally used the regression interval mapping method of Haley and Knott (1992) and the nonparametric QTL mapping approach proposed by Kruglyak and Lander (1995), both shown to be robust against the nonnormality of the phenotypes (Rebai 1997). These analyses were implemented using R/QTL (Broman et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…QTLs with a LOD score of above 2 were considered significant for further analysis (Churchill and Doerge, 1994;Doerge and Churchill, 1996). Composite interval mapping to assign significance based on the underlying trait distribution is robust at handling normal or near normal trait distributions (Rebai, 1997), as found for most of our phenotypes. The define.peak function implemented in the R/eqtl package was used to identify the peak location and one-LOD interval of each significant QTL for each trait (Wang et al, 2006).…”
Section: Qtl Analysismentioning
confidence: 55%
“…Every time a new method is developed for discrete traits, the investigator must face challenges from peers about how much improvement can be achieved if the discrete nature of the trait is ignored. These challenges repeatedly occurred and may largely credit (or blame) to the works by Visscher et al (1996) and Rebai (1997) who showed marginal improvement of GLM over LM for binary trait QTL mapping when the binary trait is treated as if it were continuous. Rao and Xu's (1998) conclusion about the ad hoc treatment of categorical trait analysis was slightly different.…”
Section: Discussionmentioning
confidence: 99%